2020
DOI: 10.21203/rs.3.rs-56863/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

iTRAQ-based Proteomic Analysis of a Chlorophyll-Deficient Mutant Caused by Single Base Change in RPS4 of Chinese Cabbage (Brassica Campestris L. ssp. Pekinensis)

Abstract: Background: Plastids are important plant-cell organelles containing a genome and bacterial-type 70S ribosomes—primarily composed of plastid ribosomal proteins and ribosomal RNAs. In this study, a chlorophyll-deficient mutant (cdm) obtained from double-haploid Chinese cabbage ‘FT’ was identified as a plastome mutant with an A-to-C base substitution in the plastid gene encoding the ribosomal protein RPS4. To further elucidate the function and regulatory mechanisms of RPS4, a comparative proteomic analysis was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
2
0
0
Order By: Relevance
“…SNOWY COTYLEDON 1 (SCO1) encodes a chloroplast-localized elongation factor G that plays a role in chloroplast development in cotyledons in Arabidopsis (Arabidopsis thaliana), but not in the Chl biosynthetic pathway [33]; the knock-out mutant of this gene has pale cotyledons. Additionally, an analysis to identify differentially expressed proteins (DEPs) in the chlorophyll-deficient mutant (cdm) of B. campestris and wild-type plants found that many ribosomal proteins, such as RPL, were up-regulated in cdm; this difference in protein abundance was consistent with a qRT-PCR analysis of gene expression [34]. As transcript abundance of these genes was related to a Chl-deficient phenotype [33,34], we used qRT-PCR to analyze expression of SCO1 (Bra027021) and RPL21 (Bra036731) in B. campestris.…”
Section: Ery and Ctc Have Different Effects On Expression Of Genes In A Tetrapyrrole Biosynthetic Pathwaysupporting
confidence: 53%
See 1 more Smart Citation
“…SNOWY COTYLEDON 1 (SCO1) encodes a chloroplast-localized elongation factor G that plays a role in chloroplast development in cotyledons in Arabidopsis (Arabidopsis thaliana), but not in the Chl biosynthetic pathway [33]; the knock-out mutant of this gene has pale cotyledons. Additionally, an analysis to identify differentially expressed proteins (DEPs) in the chlorophyll-deficient mutant (cdm) of B. campestris and wild-type plants found that many ribosomal proteins, such as RPL, were up-regulated in cdm; this difference in protein abundance was consistent with a qRT-PCR analysis of gene expression [34]. As transcript abundance of these genes was related to a Chl-deficient phenotype [33,34], we used qRT-PCR to analyze expression of SCO1 (Bra027021) and RPL21 (Bra036731) in B. campestris.…”
Section: Ery and Ctc Have Different Effects On Expression Of Genes In A Tetrapyrrole Biosynthetic Pathwaysupporting
confidence: 53%
“…Additionally, an analysis to identify differentially expressed proteins (DEPs) in the chlorophyll-deficient mutant (cdm) of B. campestris and wild-type plants found that many ribosomal proteins, such as RPL, were up-regulated in cdm; this difference in protein abundance was consistent with a qRT-PCR analysis of gene expression [34]. As transcript abundance of these genes was related to a Chl-deficient phenotype [33,34], we used qRT-PCR to analyze expression of SCO1 (Bra027021) and RPL21 (Bra036731) in B. campestris. Both of these genes are encoded in the nuclear genome.…”
Section: Ery and Ctc Have Different Effects On Expression Of Genes In A Tetrapyrrole Biosynthetic Pathwaysupporting
confidence: 53%